Cover Image, Volume 23, Issue 3. Issue 4 (18th March 2021) - Andersen, Grit; Famulla, Susanne; Heise, Tim; Ranson, Aymeric; Seroussi, Cyril; Eloy, Rosy; Gaudier, Martin; Charvet, Richard; Chan, You‐Ping; Soula, Olivier; DeVries, J. Hans
Abstract : The cover image is based on the Original Article ADO09, a co‐formulation of the amylin‐analog pramlintide and the insulin analog A21G, lowers postprandial blood glucose versus insulin lispro in type 1 diabetes (T1D) by Grit Andersen et al., https://doi.org/10.1111/dom.14302 .